2017
DOI: 10.1007/s00262-017-2085-9
|View full text |Cite
|
Sign up to set email alerts
|

A phase I vaccination study with dendritic cells loaded with NY-ESO-1 and α-galactosylceramide: induction of polyfunctional T cells in high-risk melanoma patients

Abstract: Vaccines that elicit targeted tumor antigen-specific T-cell responses have the potential to be used as adjuvant therapy in patients with high risk of relapse. However, the responses induced by vaccines in cancer patients have generally been disappointing. To improve vaccine function, we investigated the possibility of exploiting the immunostimulatory capacity of type 1 Natural killer T (NKT) cells, a cell type enriched in lymphoid tissues that can trigger improved antigen-presenting function in dendritic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 50 publications
0
39
0
1
Order By: Relevance
“…Given the fact that iNKT cells are mainly found in spleen and liver, it is logical to anticipate a higher impact upon intravenous (iv) administration as it was performed in multiple preclinical tumor models and early phase I clinical trials. 14,[28][29][30] Nevertheless, several groups also applied other administration routes and some claim to obtain better iNKT cell and NK cell activation than iv injections. 7,[16][17][18][31][32][33] Besides, the iNKT mediated help over antigen-specific T and B cell responses has not been compared in different immune compartments and administration routes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that iNKT cells are mainly found in spleen and liver, it is logical to anticipate a higher impact upon intravenous (iv) administration as it was performed in multiple preclinical tumor models and early phase I clinical trials. 14,[28][29][30] Nevertheless, several groups also applied other administration routes and some claim to obtain better iNKT cell and NK cell activation than iv injections. 7,[16][17][18][31][32][33] Besides, the iNKT mediated help over antigen-specific T and B cell responses has not been compared in different immune compartments and administration routes.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy that was suggested for the treatment of patients with solid tumors is vaccination with NKT-activating agents in combination with tumor antigens. For instance, a phase I study showed detectable NKT cell activity in patients with high-risk melanoma upon treatment with cancer/testis antigen-loaded DC in combination with α-GalCer ( 261 ). However, in our opinion, increasing the specificity of NKT cells is not the most promising method of increasing the effectiveness of NKT-based immunotherapies.…”
Section: Current Nkt Cell-based Immunotherapy For the Treatment Of Camentioning
confidence: 99%
“…Notably, multiple antibodies are in preclinical and clinical trials that target GSLs including GD2 ( 169 ), GM2 ( 170 ), Neu5GcGM3 ( 171 ), Gb3, Gb4, and Globo H ( 172 ). Another GSL, α-GalCer, has potential anti-tumor activity and is currently in phase 1 clinical trials in high risk melanoma patients ( 173 ).…”
Section: The Role Of Glycosylation In Immunotherapymentioning
confidence: 99%